Self-assembly of polymer-coated plasmonic nanocrystals : from synthetic approaches to practical applications - Lu, Derong (2020)
Self-assembly of plasmonic nanocrystals (PNCs) and polymers provides access to a variety of functionalized metallic-polymer building blocks and higher-order hybrid plasmonic assemblies, and thus is of considerable fundamental and practical interest. The hybrid assemblies often not only inherit individual characteristics of polymers and PNCs but also exhibit distinct photophysical and catalytic properties compared to that of a single PNC building block. The tailorable plasmonic coupling between PNCs within assemblies enables the precise control over localized surface plasmon resonance, which subsequently affords a series of light-driven or photo-activated applications, such as surface-enhanced Raman scattering detection, photoacoustic imaging, photothermal therapy, and photodynamic therapy. In this review, the synthetic strategies of a library of PNC-polymer hybrid building blocks and corresponding assemblies are summarized along with the mechanisms of polymer-assisted self-assembly of PNCs and the concepts for bridging the intrinsic properties of PNC-polymer assemblies to widespread practical applications.